2013
DOI: 10.1371/journal.pone.0053480
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Stress Fails to Accelerate the Onset and Progression of Plaque Pathology in the Brain of a Mouse Model of Alzheimer's Disease

Abstract: Conflicting findings exist regarding the link between environmental factors and development of Alzheimer's disease (AD) in a variety of transgenic mouse models of AD. In the present study, we investigated the effect of behavioral stress on the onset and progression of Aβ pathology in the brains of TgCRND8 mice, a transgenic mouse model of AD. One group of TgCRND8 mice was subjected to restraint stress starting at 1 month of age until they were 3 months old, while restraint stress in the second group started at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…It is reported that the struggling of mice during restraint provided increased physical activity [50]. It is possible that chronic restraint stress may result in increased physical activity judged by the longer hanging time in stressed male wild-type mice, when compared with non-stressed male mice.…”
Section: Chronic Restraint Stress Induces Motor Deficits In Atp1a3 +/−mentioning
confidence: 99%
“…It is reported that the struggling of mice during restraint provided increased physical activity [50]. It is possible that chronic restraint stress may result in increased physical activity judged by the longer hanging time in stressed male wild-type mice, when compared with non-stressed male mice.…”
Section: Chronic Restraint Stress Induces Motor Deficits In Atp1a3 +/−mentioning
confidence: 99%
“…Sandwich A␤ ELISA assay was performed as described in our previous studies [26,27]. Spinal cord at the cervical level of TgCRND8 mice was homogenized in Tris-buffered saline (20 mM Tris and 137 mM NaCl, pH 7.6) supplemented with 1% protease inhibitor cocktail (Sigma).…”
Section: Assessment Of Aβ Levelsmentioning
confidence: 99%
“…Another explanation might be that NPD‐like behavior needs to be present for a longer period in order to affect plaque pathology. One research group found that chronic stress accelerated Aβ pathology in the Tg2576 model, 74 while another group failed to show this effect in the TgCRND8 model 75 …”
Section: Discussionmentioning
confidence: 99%
“…One research group found that chronic stress accelerated Aβ pathology in the Tg2576 model, 74 while another group failed to show this effect in the TgCRND8 model. 75 …”
Section: Discussionmentioning
confidence: 99%